Single-channel cooling system design by using perforated porous insert and modeling with POD for double conductive panel - Selimefendigil Fatih; Benabdallah Faiza; Ghachem Kaouther; Albalawi Hind; Alshammari Badr M.; Kolsi Lioua (Open Physics)
In this study, a single cooling channel system is suggested for conductive double panel systems. The cooling channel for the vertical component uses perforated porous insert (PP-I) and porous insert (P-I), while cylinders are used in the PP-I case. The permeability of the porous channel (Da between 10−51{0}^{-5} and 10−11{0}^{-1}), size of the cylinders (Rc between 0 and 0.25), and location of the PP plate (Yp between 1 and 4.5) are all taken into account when calculating the effectiveness of the cooling system using finite element method. It is found that PP-I can effectively control the vortex size and enhance cooling performance, particularly for vertical plate. Nusselt number is enhanced in the absence of cylinders in the vertical channel by 92% as contrasted to 51% in the presence of cylinders. When cylinders are used for the vertical channel, the temperature drop of 13°C1{3}^{^° }{\rm{C}} is computed. The flow field noticeably changes when the permeability of the P-I and PP-I is altered. The equivalent temperature increases for P-I and PP-I with setups at Da=10−5{\rm{Da}}=1{0}^{-5} and Da=10−2{\rm{Da}}=1{0}^{-2} are 7.7°C{\text{7.7}}^{^° }{\rm{C}} and 4.4°C{\text{4.4}}^{^° }{\rm{C}}, respectively. The performance of cooling for the vertical plate is influenced favorably by the higher values of the porous plate’s vertical placement. By moving the porous object, it is possible to reduce the temperature by 8°C{8}^{^° }{\rm{C}}. For panel surface temperature, a proper orthogonal decomposition (POD)-based reconstruction model with 12 POD modes is used. The POD-based model accurately captures the effects of utilizing P-I and PP-I on the panel temperature.